2021
DOI: 10.3389/fgene.2021.626260
|View full text |Cite
|
Sign up to set email alerts
|

Delineation of Mitochondrial DNA Variants From Exome Sequencing Data and Association of Haplogroups With Obesity in Kuwait

Abstract: Background/ObjectivesWhole-exome sequencing is a valuable tool to determine genetic variations that are associated with rare and common health conditions. A limited number of studies demonstrated that mitochondrial DNA can be captured using whole-exome sequencing. Previous studies have suggested that mitochondrial DNA variants and haplogroup lineages are associated with obesity. Therefore, we investigated the role of mitochondrial variants and haplogroups contributing to the risk of obesity in Arabs in Kuwait … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 68 publications
0
12
0
Order By: Relevance
“…Interestingly, the rs8044769 at the FTO variant was found to be linked to OA via its effect on the BMI [ 43 ]. Taking into account, on the one hand, previous associations of mitochondrial background with the risk of obesity [ 44 46 ] and, on the other hand, the differential methylation pattern between haplogroups H and J in cartilage in genes related to developmental processes, including the homeobox family [ 64 ], potential interactions between haplogroup H/cluster HV able to modify the risk of structural progression in OA are not surprising.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the rs8044769 at the FTO variant was found to be linked to OA via its effect on the BMI [ 43 ]. Taking into account, on the one hand, previous associations of mitochondrial background with the risk of obesity [ 44 46 ] and, on the other hand, the differential methylation pattern between haplogroups H and J in cartilage in genes related to developmental processes, including the homeobox family [ 64 ], potential interactions between haplogroup H/cluster HV able to modify the risk of structural progression in OA are not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…A dominant model of the risk alleles was used to assess the influence of the SNPs as we assume that one copy of the risk allele is enough to modify the risk. The factors, age and BMI, were included as in addition to being interconnected with structural OA [38][39][40], some genetic polymorphisms, as well as mtDNA variants, have been found associated with these factors [41][42][43][44][45][46][47].…”
Section: Model Developmentmentioning
confidence: 99%
“…Kuwaiti population (288 whole-exome) identified 1,241 mtDNA SNPs [158]. Qatari (n=864) population based mitogenome analysis 1831 mtDNA variants including 56 indels and 1775…”
Section: P R E P R I N Tmentioning
confidence: 99%
“…The study revealed 968 variations in the mtDNA genome in 15 haplogroups. Another study on the mitogenome of the Kuwaiti population (288 whole-exome) identified 1,241 mtDNA SNPs [ 158 ]. In a Qatari ( n = 864) population mitogenome analysis of 1831 mtDNA variants including 56 indels and 1775 SNPs was performed [ 159 ].…”
Section: Mitogenomementioning
confidence: 99%
“…Over the last decades, the extensive study of mitochondrial genetics has provided evidence that impairments in mitochondrial DNA are linked with various pathological conditions (Dashti et al, 2021). Genes presented in mtDNA encode transcripts for independent protein synthesis in mitochondria as well as proteins involved in oxidative phosphorylation (Onyango et al, 2016).…”
Section: Introductionmentioning
confidence: 99%